Analisis Bangkitan Pada Ruas Jalan Pasca Pembangunanan Apartemen Begawan Di Jl. Raya Tlogomas, Kota Malang - Ndapakamang, Aronot Delta; Yurnalisdel, Yurnalisdel; Oktaviastuti, Blima (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Transportation plays an important role in people's lives because it can facilitate daily activities. The existence of transportation can connect one area with another. Roads are very important traffic facilities for community mobilization. One part of the road infrastructure is the intersection, which is the meeting point of each road section. This can make the performance of an intersection affect the performance of the road section as a whole. The purpose of this study is to determine traffic generation, road section performance, and analyze the volume of traffic flow in the next 5 years on the tlogomas road section. This is due to the high volume of vehicles on Jalan Raya Tlogomas which often causes congestion. From these problems, it is necessary to study the performance of Jalan Raya Tlogomas by calculating traffic volume, capacity and degree of saturation. The existing road at the research location has a road body width of 9 m, namely with 2 two-way lanes so that each lane is 4.5m and a 1.00-m road shoulder. In this study the data taken is the volume of movement generation in the Begawan apartment which amounted to 704-units and 868-units of vehicles, the volume performance of the tlogomas road section which shows that the peak hour on Friday, June 30, 2023 (Dinoyo -Batu) at 07:00-08:00 and (Batu-Dinoyo) at 13:00-14:00. Based on the results of the calculation obtained the total flow of 89359 smp / hour, the capacity value (C) 2599 skr / hour and the degree of saturation (DJ) 2.25 has exceeded the DJ value required in PKJI 2014 which is DJ≥1.00 and the level of service is F (Very Bad).